Analisis kemampuan literasi matematis siswa kelas VIII SMP ditinjau dari perbedaan gender - Sari, Dian Ulfa (Jurnal Pendidik Indonesia, 2022)
This study aims to see the ability of mathematical literacy in class VIII female students and male students of SMP Negeri 2 Kendari. This exploratory research aims to obtain a description/explanation of the mathematical literacy abilities of junior high school students. Student literacy was observed by looking at (reviewing) the results of the interviews. Next, the process of students building mathematical literacy skills is examined. The subjects in this study consisted of one male student and one female student, with the criteria of students being able to communicate their ideas or thoughts both orally and in writing. Based on the results of data processing and discussion in this study, several conclusions were obtained as follows: (1) Female students with mathematical literacy abilities on three-stage quantity content, on space and shape content students were able to go through five stages, and on change and relationships content students able to go through one stage. While male students with mathematical literacy skills in quantity content were able to go through two stages, in space and shape content, students were able to go through four stages. In change and relationships content, students could go through all stages.